Synthesis and Biological Evaluation of Pyrazole Derivatives as Anti-Amyloid and Anti-Inflammatory Agents for Alzheimer’s Therapy - Mansi Mishra; Sushma Verma; Khushboo Mishra; Anita D. Kadam; Souvik Sur; Gayatri Katole; Rashmi Sharma; Ajay Kumar Yadav; Jannat Ul Firdaus (Oriental Journal Of Chemistry, 2026)
Alzheimer's disease (AD) remains a devastating neurodegenerative disorder with no disease-modifying therapies available, largely due to its complex, multifactorial pathophysiology involving amyloid β (Aβ) aggregation, tau hyperphosphorylation, chronic neuroinflammation, oxidative stress, and proteasomal dysfunction. This review comprehensively evaluates the synthesis and biological evaluation of pyrazole derivatives as promising multi-target-directed ligands (MTDLs) for Alzheimer's therapy. The pyrazole scaffold, with its exceptional structural versatility and ease of synthetic modification, has enabled the rational design of diverse compound classes targeting multiple AD-relevant pathways simultaneously. Diphenylpyrazoles function as non-competitive β-secretase (BACE1) modulators, selectively suppressing Aβ production while preserving essential physiological enzyme activity, with the lead compound Anle138b demonstrating remarkable ability to block Aβ pore activity, restore synaptic function, and improve memory in transgenic AD mouse models. Arylpyrazolones (exemplified by compound 1, EC₅₀ = 270 nM) exhibit potent anti-amyloidogenic activity with excellent blood-brain barrier permeation and favorable oral bioavailability. Ferrocene-pyrazole-curcumin analogues show structure-dependent anti-amyloidogenic activity validated by thioflavin T fluorescence and atomic force microscopy, combining natural product inspiration with organometallic fine-tuning. Regarding tau pathology, acylaminopyrazoles inhibit glycogen synthase kinase-3β (GSK-3β) in the low micromolarrange, preventing tau hyperphosphorylation and neurofibrillary tangle formation, while pyrazolones enhance ubiquitin-proteasome system activity, promoting clearance of misfolded proteins and protecting neurons from amyloid-induced toxicity. The collective evidence positions pyrazole-based MTDLs as a chemically feasible, pharmacologically versatile platform for addressing the intricate crosstalk among amyloid pathology, tauopathy, neuroinflammation, and proteostasis failure in Alzheimer's disease, offering genuine hope for next-generation disease-modifying therapeutics.